Studies on mechanical, electrical and physical properties of recycled hdpe reinforced with woodflour nanoclay/microclay - Mohanraj, R.; Soundararajan, S.; Palanivelu, K. (Penerbit Universiti Kebangsaan Malaysia, 2024)
In this project we are using recycled HDPE along with woodflour as particulate filler and nanoclay/microclay to study the performance of these wood plastics composites. Recycled HDPE was melted-blended with wood flour (10%,20%&30%) using the twin screw compounding extruder. Also nano clay (1% and 3%) was added with recycled HDPE containing 30% wood flour and also microclay (1%, 3%, 5% and 7%) was added with nanoclay 3% containing recycled HDPE with 30% wood flour. PE-g-MAH was added as compatibilizer. The test specimens were prepared by injection molding machine as per ASTM standards. The mechanical, electrical, and physical properties were evaluated. The test results of wood plastics composites made with recycled HDPE indicated that the mechanical properties like tensile strength, tensile modulus, flexural strength, flexural modulus, and hardness are improved. The elongation at break and izod impact strength were lowered. Wood flour (30%) reinforced recycled HDPE has higher mechanical properties with optimum impact strength than other formulations with and without nanoclay/microclay. Electrical properties like volume resistivity, surface resistivity, arc resistance and dielectric strength were decreased as the wood flour content was increased. The melt flow index was decreased, density increased. The mechanical properties of wood recycled plastics composites were not affected or improved when nanoclay was used, when microclay was added then the tensile strength was little lowered and other mechanical properties were better than recycled HDPE but lower than wood plastic composites with and without nanoclay.